Mobility Analysis of Persons with Disabilities - Miodrag Počuč; Valentina Mirović; Jelena Mitrović Simić; Caglar Karamasa (Discrete Dynamics in Nature and Society)
This study presents the results of the research on travel behaviour for persons with different types of disabilities. Persons with disabilities are a group of participants with specific traffic requirements often not included in traffic research and consequently adequate planning of urban transport. To obtain the data, a home interview was conducted on a representative sample. The paper presents the main results of the research and indicates the specificity of the requirements of this group of users. The results are compared with the results of the same research conducted for the development of the Smart Plan of Novi Sad and the results of similar research abroad. The main goal is to obtain a qualitative and quantitative database of the requirements of this group of users as a basis for creating sustainable urban mobility plans.